Individualised gonadotrophin ovulation induction in women with normogonadotrophic anovulatory infertility: A prospective, observational study. (March 2017) - Lauritsen, Mette Petri; Loft, Anne; Pinborg, Anja; la Cour Freiesleben, Nina; Cohen, Arieh; Petersen, Jørgen Holm; Mikkelsen, Anne Lis; Bjerge, Marianne Rich; Nyboe Andersen, Anders
Abstract: Objective: The aim of this study was to evaluate an individualised gonadotrophin starting dose regimen for women with anovulatory infertility. Study design: We included 71 normogonadotrophic anovulatory infertile women in a prospective, observational study. All underwent one ovulation induction cycle in a flexible, low-dose step-up protocol. The gonadotrophin starting dose (75–150 IU/day) was individualised according to a nomogram incorporating menstrual cycle pattern (oligo- or amenorrhoea), BMI, and mean ovarian volume. The number of women who fulfilled the criteria for human chorionic gonadotrophin (hCG) administration (one follicle ≥17 mm or 2–3 follicles ≥15 mm) was assessed. Results: Of the 50 women (70.4%) who fulfilled the hCG criteria and underwent intrauterine insemination, 34 (47.9%) achieved monofollicular growth and 16 (22.5%) developed 2–3 mature follicles. Seventeen (23.9%) cycles were converted to in vitro fertilisation (IVF) due to the development of >3 mature follicles, and one (1.4%) cycle was cancelled due to risk of ovarian hyperstimulation syndrome. Baseline total antral follicle count was found to be significantly associated with fulfillment of the hCG criteria (OR 0.96, 95% CI: 0.92–0.99, P  = 0.01). Conclusions: The nomogram-based dose regimen was not considered suitable for ovulation induction due to a tendency to overestimate the gonadotrophin starting dose. However, the model may serve as a mild IVF regimen, especially in women prone to excessive follicle growth.